Security with Intelligent Computing and Big-Data Services 2019 : Proceedings of the 3rd International Conference on Security with Intelligent Computing and Big-data Services (SICBS), 4–6 December 2019, New Taipei City, Taiwan /: Proceedings of the 3rd International Conference on Security with Intelligent Computing and Big-data Services (SICBS), 4–6 December 2019, New Taipei City, Taiwan. (2020) - Unknown
No abstract available